Program Correctness through Self-Certification. - Namjoshi, Kedar S.; Zuck, Lenore D. (Communications of the ACM, 2025)
The article discusses program correctness through self-certification as an alternative to verification or testing. The authors note there are two main verification techniques, deductive proofs and model checking. They explore how self-certification establishes the correctness of every individual program execution by generating and checking certificates.